2017
DOI: 10.1155/2017/1758139
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Extracellular Vesicles: Roles in Tumor Growth, Progression, and Drug Resistance

Abstract: Mesenchymal stem cells (MSCs) are ubiquitously present in many tissues. Due to their unique advantages, MSCs have been widely employed in clinical studies. Emerging evidences indicate that MSCs can also migrate to the tumor surrounding stroma and exert complex effects on tumor growth and progression. However, the effect of MSCs on tumor growth is still a matter of debate. Several studies have shown that MSCs could favor tumor growth. On the contrary, other groups have demonstrated that MSCs suppressed tumor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 79 publications
0
47
0
Order By: Relevance
“…It is a chemokine which can attract various progenitor cells, stem cells, leukocytes, neurons, angioblast/endothelial cells, and tumor cells. Thus it is involved in plenty of processes such as angiogenesis, hematopoiesis, and tissue repair (e.g., myocardial infarction (MI) and ischeamic stroke) (Bromage, Davidson, & Yellon, 2014;Kubota et al, 2016;Yang et al, 2018;Zhang et al, 2017). CXCL12/SDF-1 acts through the G protein-coupled CXCR4.…”
Section: Cytokines Chemokines and Peptide Hormonesmentioning
confidence: 99%
“…It is a chemokine which can attract various progenitor cells, stem cells, leukocytes, neurons, angioblast/endothelial cells, and tumor cells. Thus it is involved in plenty of processes such as angiogenesis, hematopoiesis, and tissue repair (e.g., myocardial infarction (MI) and ischeamic stroke) (Bromage, Davidson, & Yellon, 2014;Kubota et al, 2016;Yang et al, 2018;Zhang et al, 2017). CXCL12/SDF-1 acts through the G protein-coupled CXCR4.…”
Section: Cytokines Chemokines and Peptide Hormonesmentioning
confidence: 99%
“…It has been suggested that these vesicles are secreted by a variety of cell types and can function as intercellular transmitters of mRNA, microRNA, and proteins [83]. They are thought to mimic the roles played by mesenchymal stem cells from which they originate [84, 85]. The importance of ASC-secreted exosomes in promoting tissue repair has been reported.…”
Section: Adipose Tissue-derived Mesenchymal Stem Cell Characteristicsmentioning
confidence: 99%
“…Engineered EVs or EVs from healthy subjects can transport biologically active anti-cancer molecules, that in turn regulate gene expression and cellular function in target cells [21]. In particular, the administration of MSC-derived EVs exerts various effects on the development and progression of different type of cancers [22,23]. The safety and feasibility observed in early clinical trials using MSCs has resulted in an increased interest in the translation of the use of these cells to the clinic [24].…”
Section: Discussionmentioning
confidence: 99%